The effect of supplements containing different protein and energy sources and essential oils on the performance of pasture finished heifers - Engelbrecht, Michiel Nicolaas (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.